Assessing quality of newborn care at district facilities in Malawi - Kondwani Kawaza; Mai-Lei Woo Kinshella; Tamanda Hiwa; Jenala Njirammadzi; Mwai Banda; Marianne Vidler; Laura Newberry; Alinane Linda Nyondo-Mipando; Queen Dube; Elizabeth Molyneux; David M. Goldfarb (BMC, 2020)
Abstract Background Malawi is celebrated as one of the few countries in sub-Saharan Africa to meet the Millennium Development Goal of reducing under-5 mortality by two-thirds between 1990 and 2015. However, within this age range neonatal mortality rates are the slowest to decline, even though rates of facility births are increasing. Examining the quality of neonatal care at district-level facilities where most deliveries occur is warranted. Objective The objective of this paper is to evaluate the quality of neonatal care in three district hospitals and one primary health centre in southern Malawi as well as to report the limitations and lessons learned on using the WHO integrated quality of care assessment tool. Methods These facility assessments were part of the "Integrating a neonatal healthcare package for Malawi" project, a part of the Innovating for Maternal and Child Health in Africa (IMCHA) initiative. The WHO integrated quality of care assessment tool was used to assess quality of care and availability and quantity of supplies and resources. The modules on infrastructure, neonatal care and labour and delivery were included. Facility assessments were administered in November 2017 and aspects of care were scored on a Likert scale from one to five (a score of 5 indicating compliance with WHO standards of care; one as lowest indicating inadequate care). Results The continuum of labour, delivery and neonatal care were assessed to identify areas that required improvements to meet standards of care. Critical areas for improvements included infection control (mean score 2.9), equipment, supplies and setup for newborn care in the labor ward (2.3), in the surgical theater (3.3), and nursery (3.4 nursery facilities, 3.0 supplies and equipment), as well as for management of sick newborns (3.2), monitoring and follow-up (3.6). Only one of the 12 domains, laboratory, met the standards of care with only minor improvements needed (4.0). Conclusion The WHO integrated quality of care assessment tool is a validated tool that can shed light on the complex quality of care challenges faced by district-level health facilities. The results reveal that the quality of care needs improvement, particularly for sick and vulnerable newborns.